2020
DOI: 10.1177/1078155220942292
|View full text |Cite
|
Sign up to set email alerts
|

Rapid desensitization to brentuximab vedotin after severe anaphylaxis in the treatment of refractory Hodgkin’s lymphoma

Abstract: Introduction Brentuximab vedotin is a monoclonal antibody drug conjugate used for the treatment of patients with Hodgkin lymphoma. Hypersensitivity reactions to brentuximab vedotin may include cutaneous, cardiovascular, respiratory, gastrointestinal and neurological signs and symptoms. Case report We present the case of a 23-year-old Mexican female with stage IV progressive classical nodular sclerosing Hodgkin lymphoma who received multiple previous chemotherapy regimens. Brentuximab vedotin at 1.8 mg/kg (180 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Previous research trials have shown that when patients are carefully chosen concerning the type of reactions and are stratified according to risk, desensitization is a valuable alternative to allow patients to remain on first-line therapies, improving their prognosis and quality of life. [11][12][13][14][15][16] In these patients, desensitization allowed patients to achieve remission of treatment-refractory Hodgkin Lymphoma and thus be candidates for hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research trials have shown that when patients are carefully chosen concerning the type of reactions and are stratified according to risk, desensitization is a valuable alternative to allow patients to remain on first-line therapies, improving their prognosis and quality of life. [11][12][13][14][15][16] In these patients, desensitization allowed patients to achieve remission of treatment-refractory Hodgkin Lymphoma and thus be candidates for hematopoietic cell transplantation.…”
Section: Discussionmentioning
confidence: 99%